Nogeens: watter kerk vergesél die Groot Trek? - P. J. Strauss (Acta Theologica)
It is sometimes argued that the Great Trek of 1835-1840 removed its participants from the Cape Colony, under British control, thereby also taking them out of the congregations of the Dutch Reformed Church (DRC) based in the Cape. The argument further goes that the church which accompanied the Great Trek was a church independent of the DRC. In this article, documents and arguments show that the church on the Great Trek was indeed the DRC. This is shown by the name used for the church in transit, by the religious customs of the members of this church, and by the relationships of individuals with DRC congregations in the colony. Congregations outside the Transvaal, which were founded by the Trekkers, had no problems to become part of the DRC Synod of the Cape. Before they left the Cape Colony, some Trekkers were members of congregations of this selfsame DRC Synod.